Penggunaan “Gudang Teks” Sebagai Digitalisasi Teks Negosiasi Berbasis Google Sites dalam Menunjang Pembelajaran Bahasa Indonesia - Khansa Hafidza; Rachel Fatma Maharani Putri; Alvin Demas Arethusa; Sri Hastuti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In the current era, digital learning media began to be developed along with the rapid development of information technology. Educators are indirectly required to make adjustments to the development of information technology-based learning media. Gudang Teks is a Indonesian learning media program designed through the world wide web precisely on google-sites which is a place for storage of negotiation text materials. With this, this study was conducted to analyze information technology-based learning media on the use of LMS in the form of google-sites under the name